Case report: A case of advanced gastric cancer with multiple skin metastases, with significant relief from immunotherapy - Hao, Wen; Chang, Ruimin; Liu, Jingxin; Wang, Yibing; Ren, Meijin; Xin, Kai; Liu, Baorui; Xie, Jiaqi; Yang, Yang (Frontiers in Immunology, 2024)
Gastric cancer is the fifth leading cause of cancer-related mortality worldwide, with a low 5-year survival rate in advanced stages. Cutaneous metastasis is rare in gastric cancer, with only 0.8-1% incidence. We reported a rare case of female gastric cancer. The patient had undergone subtotal gastrectomy and chemotherapy 13 years ago, followed by a subsequent surgery of residual stomach, partial jejunum, and partial colon resection 11 years later. The pathological examination revealed poorly differentiated stomach adenocarcinoma, Lauren classification: diffuse type. The patient received 2 cycles of SOX chemotherapy. Two years later, cauliflower-like skin nodules, which were surgically excised, appeared on the back. The histopathological examination showed a spindle cell tumor; no specific anti-tumor treatment was administered. Six months later, the skin lesions increased in size and number, spreading to the neck, chest, and abdomen, presenting as erythematous patches with some cauliflower-like elevations. A skin biopsy of a 1cm0.5cm0.3cm lesion on the left abdomen was performed, and based on the immunohistochemistry, clinical history, and the possibility of metastatic or infiltrating adenocarcinoma, the gastrointestinal origin was highly suspected. Genetic testing was performed on the gastric recurrence and skin lesions, revealing 103 shared genetic variations, further suggesting the skin metastasis originated from gastric cancer. Subsequently, the patient received 10 cycles of immunotherapy combined with intravenous chemotherapy (200mg Tislelizumab and 100mg albumin-bound paclitaxel). The treatment response was evaluated as partial remission, with significant improvement in the skin lesions compared to before. This case highlights the possibility of tumor metastasis in patients with extensive skin lesions in advanced gastric cancer. Early examination, diagnosis, skin biopsy, immunohistochemistry, and genetic sequencing are recommended.